The Vaca Muerta transgression (Upper Jurassic), Neuquén Basin, Argentina: Insights into the evolution and timing of aeolian-marine transitions - Paz, Maximiliano (2021)
Fil: Carmona, Noelia Beatriz. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro; Argentina.